Gender Interaction Pattern on Private Television Channels’ Turkish & Pakistani Dramas and Viewers Perception - Madni, Abdul Rehman; Hassan, Shajee; Aziz , Faisal; Amin, Salman (Asian Journal of Empirical Research, 2014)
Drama is a more effective source of informing, educating, guiding & entertaining people. The current study was conducted to measure watching habits of female viewers of Sargodha city and aim of this study was also explored female viewers’ perception regarding Turkish and Pakistani dramas of private television channels. Having in mind the importance and requirement of this present study survey research method was chosen. For this current research effort female students, working women and housewives of Sargodha city were taken as Universe of the Study. Stratified sampling was adopted to divide the population into different strata i.e. students, working women and housewives and then sample size of 300 was chosen by using the purposive technique of sampling. The findings of this research effort showed that overall all sub groups prefer to watch Hum TV than other channels. Results also indicated that Turkish dramas present more mix gathering, joint office work, drinking habits in parties, dancing, hand shaking, kissing, and modeling then Pakistani dramas.